PENDIDIKAN UNTUK MENYAMBUT MASYARAKAT 5.0 - Rohim, Herli; Darwanto, Darwanto (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract—The development of the world of education is entering a very important period. Not only in an effort to provide quality and optimal education services. But it is also an important period that will determine the continuation of education itself. Today, the challenges in education are increasingly complex and require very serious preparation and thinking. We are faced with a rapid and non-linear change. This is as a result of the rolling of the Industrial Revolution 4.0 era. These technological advancements enable automation in almost all fields. As we know, the first generation industrial revolution was marked by the use of steam engines to replace human and animal power. The second generation, through the application of the concept of mass production and the use of electricity. The third generation, marked by the use of automation technology in industrial activities. In the fourth industrial revolution, it became a big leap for the industrial sector, where information and communication technology was fully utilized. The hustle and bustle of the Industrial Revolution 4.0, which was accompanied by the development of a disruption era, was suddenly shocked by the emergence of Society 5.0 (community 5.0). The concept of Society 5.0 has actually been rolling for a long time. This concept appears in the